Carrier Aggregation Technique to Improve Capacity in LTE-Advanced Network - Iskandar Iskandar; R. Galih (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Carrier aggregation (CA) is a major feature in LTE-advanced technology that allows network provider to use more than one carrier simultaneously to increase capacity. CA uses two or more individual component carriers (CCs) of the same (intra-band) and different (inter-band) frequency bands. In this paper, we evaluate CA techniques with the test parameter using BLER and throughput inside the tested area of LTE network. The tested area is designed to represent most common environment in which LTE will be deployed. We use 30 MHz frequency bandwidth in the simulation to evaluate intra-band and inter-band CA technique performance. Two CCs is allocated for primary serving cell (PCell) and secondary serving cell (SCell). Simulation result shows for the downlink, BLER tend to increase, as the frequency configuration is increase. However, for the uplink BLER is zero. We found that for CA configuration with wider PCell bandwidth resulting better throughput. In CA intra-band, the throughput of non-contiguous CA is better than CA contiguous. Then in the inter-band CA, CC combination with a lower frequency produces higher throughput.